Smoldering and Flaming of Disc Wood Particles Under External Radiation: Autoignition and Size Effect - Wang, Supan; Ding, Pengfei; Lin, Shaorun; Gong, Junhui; Huang, Xinyan (Frontiers in Mechanical Engineering, 2021)
Wildfires are global issues that cause severe damages to the society and environment. Wood particles and firebrands are the most common fuels in wildfires, but the size effect on the flaming and smoldering ignitions as well as the subsequent burning behavior is still poorly understood. In this work, a well-controlled experiment was performed to investigate smoldering and flaming ignitions of stationary disc-shaped wood particles with different diameters (25–60 mm) and thicknesses (15–25 mm) under varying radiant heat flux. The ignition difficulty, in terms of the minimum heat flux, increases from smoldering ignition to piloted flaming ignition and then to flaming autoignition. As the sample thickness increases, the minimum heat flux, ignition temperature, and burning duration for flaming autoignition all increase, while the peak burning flux decreases, but they are insensitive to the sample diameter. During ignition and burning processes, the disc particle is deformed due to the interaction between chemical reactions and thermomechanical stresses, especially for smoldering. The characteristic thickness of the smoldering front on wood is also found to be 10–15 mm. This study sheds light on the size effect on the ignition of wood particles by wildfire radiation and helps understand the interaction between flaming and smoldering wildfires.